Designing agrivoltaic systems to optimize crop productivity and energy generation - Sim, Yang Hong (2025)
Agrivoltaics integrates agricultural production with photovoltaic (PV) energy generation, offering a potential solution to the increasing competition for land between food and energy sectors. This study focuses on the design and optimisation of an agrivoltaic system to maximise both crop yield and solar power generation. The implementation of PV panels, however, introduces shading effects that can alter crop’s growth performance. To address this, different PV layouts were designed and evaluated through PVsyst simulations and controlled experimental trials. Crop growth performance under varying shading levels was assessed alongside energy yields to determine the most efficient system configuration. Results indicate that a tilt angle of 15° is optimal for Malaysian conditions, as it minimises thermal losses while balancing energy output and crop productivity. A full-density solar configuration achieved the highest annual electricity generation (702.93 MWh) but significantly reduced crop growth performance. Conversely, a half-density solar configuration provided more favourable growing conditions, with partially shaded crops recording the highest growth performance index (0.60), followed by open-field crops (0.50) and heavily shaded crops (0.19) by recorded the variables such as number of fruits, average fruit diameter, height and number of new leaves per week and conducted Multi Criteria Analysis. The integration scenario combining half-density PV arrays with partially shaded crops produced the highest Land Equivalent Ratio (LER) of 1.64, highlighting superior land-use efficiency compared to full-density arrays (LER = 1.38). For the case study of Hami EcoFarm, prioritising agricultural productivity while maintaining sustainable energy output suggests that the half-density configuration represents the most suitable implementation strategy.